Embolization with microspheres alone for hepatocellular carcinoma with portal vein tumor: analysis of outcome and liver function at disease progression. Issue 4 (April 2020) - Borgheresi, Alessandra; Covey, Anne; Yarmohammadi, Hooman; Boas, Franz E.; Ziv, Etay; Getrajdman, George; Erinjeri, Joseph; Jarnagin, William; Harding, James J.; D'Angelica, Michael; Gonen, Mithat; Brown, Karen T.
Abstract: Background: This retrospective study reviews long-term outcome of hepatic artery embolization (HAE) using microspheres alone in patients presenting with Hepatocellular Carcinoma (HCC) and portal vein tumor (PVT). Methods: From 2005 to 2015, 43 patients with HCC and PVT underwent HAE. Response to treatment, time-to-progression (TTP), local-tumor-progression (LTP), distant-hepatic-progression (DHP), PVT-progression (PVTP), and/or the development of extra-hepatic progression (EHP) were assessed on pre-HAE CT/MRI scans, within 4 weeks post-HAE and at quarterly intervals thereafter, along with liver function (Child-Pugh score, CP). Results: Forty (40/43) patients progressed during a median follow-up of 10 months with a median TTP of 2.9 months. Eleven of the 40 patients (27.5%) developed EHP, with only 2 patients (5%) demonstrating solely LTP. Six patients (15%) developed PVTP only. At progression, 27 patients (27/40, 77%) maintained their initial CP status, including all 5 CP-B patients. Median survival was 12.5 (95% CI 8–23) months for the entire group; 17.3 (95% CI 10–33) months for the patients with segmental/lobar PVT, compared with 8.4 (95% CI 6–13) months for the patients with main PVT (p = 0.02). Conclusion: HAE can be used to treat patients with HCC and PVT with median survival of approximately a year and preserved liver function.